Demand Uncertainty and the Capital-Labor Ratio: Evidence from the U.S. Manufacturing Sector - Ghosal, Vivek (The Review of Economics and Statistics, 1991)
Richard Hartman (1976) and Duncan M. Holthausen (1976) showed that firms' input choices may be affected by demand uncertainty. Specifically, uncertain demand conditions may lead to firms operating with a lower capital-ratio. This result has potentially important implications for the analysis of factor demand and factor productivity. The author constructs measures of demand uncertainty and examines the above relationship for a sample of 125 U.S. manufacturing industries. Results show that there exists a significant negative relationship between demand uncertainty and the capital-labor ratio. Copyright 1991 by MIT Press.